Triglyceride glucose index, pediatric NAFLD fibrosis index, and triglyceride-to-high-density lipoprotein cholesterol ratio are the most predictive markers of the metabolically unhealthy phenotype in overweight/obese adolescent boys - Furdela, Viktoriya; Pavlyshyn, Halyna; Shulhai, Anna-Mariia; Kozak, Kateryna; Furdela, Mykhailo (Frontiers in Endocrinology, 2023)
Introduction: The prevalence of obesity constantly increases worldwide and definitely increases the risk of premature death in early adulthood. Whereas there is no yet treatment with proven efficacy for the metabolic clamp such as arterial hypertension, dyslipidemia, insulin resistance, diabetes type 2, and fatty liver disease, it is imperative to find a way to decrease cardiometabolic complications. Early prevention strategies beginning in childhood are the most logical step to reduce future cardiovascular morbidity and mortality. Therefore, the current study is aimed to determine the most sensitive and specific predictive markers of the metabolically unhealthy phenotype with high cardiometabolic risk in overweight/obese adolescent boys. Methods: This study was carried out at the Ternopil regional hospital (Western Ukraine) and involved 254 adolescent overweight or obese boys [median age was 16.0 (15.0-16.1) years] randomly chosen. A control group of 30 healthy children with proportional body weight comparable in gender and age to the main group was presented. A list of anthropometrical markers with biochemical values of carbohydrate and lipid metabolism with hepatic enzymes was determined. All overweight/obese boys were divided into three groups: 51.2% of boys with metabolic syndrome (MetS) by IDF criteria, 19.7% of boys metabolically healthy obese (MHO) without hypertension, dyslipidemia, and hyperglycemia, and the rest of boys (29.1%) were classified as metabolically unhealthy obese (MUO) who have only one criterion (hypertension, dyslipidemia or hyperglycemia). Results: Based on multiple logistic regression analysis which included all anthropometric, biochemical values and calculated indexes in boys from the MHO group and MetS, it was detected that the maximum likelihood in the prediction of MetS makes Triglyceride glucose index, pediatric nonalcoholic fatty liver disease fibrosis index (PNFI) and Triglyceride to high-density lipoprotein cholesterol ratio (R2 =0.713, p<0.000). Tracing the Receiver operating characteristics curve, the model is confirmed as a good predictor of MetS (AUC=0.898, Odds ratio=27,111 perc. correct=86.03%) in overweight and obese boys. Conclusions: Triglyceride glucose index, pediatric NAFLD fibrosis index, and Triglyceride to high-density lipoprotein cholesterol ratio is a valuable combination of predictive markers of metabolically unhealthy phenotype in Ukrainian overweight/obese boys.